Evaluation of Information System X Users Using the HOT-Fit Method at RSUD X in 2026 - Rasya Fadia Rohim; Yanto Haryanto; Bhakti Aryani; Fitria Dewi Rahmawati (CV. Inara, 2026)
Digital transformation in the healthcare sector demands optimization of the Hospital Management Information System (SIMRS), including system information X at RSUD X, which still faces technical and usability challenges. This study aims to analyze the relationship between human, organizational, and technological factors and net benefits using the HOT-Fit model. The study used a quantitative, analytical descriptive design with a cross-sectional approach. The population was 117 SIMRS users with a sample of 91 respondents using the proportionate stratified random sampling technique. The research instrument was a 38-item Likert questionnaire that had been tested for validity and reliability. Data analysis was performed univariately and bivariately using the Spearman correlation test. The results showed that all variables had a significant relationship with net benefits, with moderate strengths for human (r=0.560) and organizational (r=0.573), and strong for technology (r=0.659). In addition, most respondents gave positive assessments on all HOT-Fit dimensions, although there were still obstacles in access speed and technical services. The conclusion of this study shows that technological factors are the main determinant in increasing SIMRS benefits, supported by the role of human and organizational factors. System optimization requires infrastructure improvements, ongoing training, and consistent organizational support.